A finite element analysis on combined convection and conduction in a channel with a thick walled cavity. Issue 8 (28th October 2014) - Rahman, M.M.; Oztop, Hakan; Mekhilef, S.; Saidur, R.; Chamkha, A.; Ahsan, A.; S. Al-Salem, Khaled
Abstract : Purpose: – The purpose of this paper is to examine the effects of thick wall parameters of a cavity on combined convection in a channel. In other words, conjugate heat transfer is solved. Design/methodology/approach: – Galerkin weighted residual finite element method is used to solve the governing equations of mixed convection. Findings: – The streamlines, isotherms, local and average Nusselt numbers are obtained and presented for different parameters. It is found heat transfer is an increasing function of dimensionless thermal conductivity ratio. Originality/value: – The literature does not have mixed convection and conjugate heat transfer problem in a channel with thick walled cavity.